Virgin olive oil processing by high voltage electrical discharge or high hydrostatic pressure. Issue 9 (29th March 2022) - Angeloni, Giulia; Guerrini, Lorenzo; Breschi, Carlotta; Zanoni, Bruno; Calamai, Luca; Parenti, Alessandro; Masella, Piernicola
Abstract: We test the application of two emerging technologies to virgin olive oil (VOO) processing. high voltage electrical discharge (HVED) was tested at 20 kV and about 100 kJ/kg of VOO. High‐pressure processing (HPP) was applied for 360 s at about 600 MPa. VOO quality indices were evaluated immediately after treatment and after 6 months. The HPP treatment was found to have no negative influence on any aspect ( p  > .05 according to General Linear Model and the Tukey HSD test). The HVED treatment did not affect conventional quality indices ( p  > .05), but was consistent with the appearance of secondary oxidation products (anisidine value increment of about 50% and rDigs increment of roughly 200%, both at p  ≤ .05), a significant fall in biophenol concentrations roughly from 5 to 10% at p  ≤ .05; and a decrease of about 15% at p  ≤ .05 in positive volatiles. Overall, HVED processing appears to negatively impact VOO quality. Novelty impact statement: For the first time, high voltage electrical discharge (HVED) has been tested on virgin olive oil (VOO) in comparison to high‐pressure processing (HPP) over a storage period While HPP was entirely safe for VOO quality, HVED determines a potential detrimental effect Our findings support the application of these technologies to food containing VOO, or for its direct treatment, for instance, to protect against microbial spoilage.